Judicial litigations and social welfare: access to medicines in two towns in the Santa Catarina State, Brazil - 10.4025/actascihealthsci.v34ispec.10084 - Leite, Silvana Nair; Schaefer, Cristine; Fittkau, Kelli (Acta Scientiarum. Health Sciences, 2012)
The growing number of lawsuits to obtain free medicines from the Brazilian Health System (SUS) is analyzed to characterize the supply of the requested drugs in two towns with different social and economic characteristics and different municipal pharmaceutical assistance organizations. Data for 2006 and 2007 were collected from the archives of the Municipal Health of Blumenau and Social Welfare Department of Aurora, two towns in the state of Santa Catarina, Brazil. The number of patients assisted in both towns was similar in 2007 (115 in Aurora and 160 in Blumenau). A total of 0.53/1,000 inhabitants sought this kind of access in Blumenau, with an average cost of R 2,503.29 and R 1.33 per capita; in Aurora, 21.29 users/1,000 inhabitants sought the service, with an average cost of R 101.63 and R 2.14 per capita. In Blumenau, cardiovascular medicines were the most requested, mostly from specialist physicians; in Aurora, drugs that act on the central nervous system were the most prescribed, mainly by FHP physicians. The differences evidenced the situation of the pharmaceutical organization in the two towns and their level of organization with regard to the public health system.